(3GdCUhd aj TQM GdaUhd dCHbQGWs - (3jYbhH Hf ESMGb GdeSjMj Gdedcj GdcQcj GHf Gdba, CHh GdaQL,J (B685 (3g` s
(3ChdgG (B:s
(3hHYO abO(B: (3SCdfi HYV ef jTGZd Ydi Cf CTQM dg cJGH GdaUhd ddEeGe EHbQGW bOS Gddg dWag hfhQ VQjMI s
(3BNQgG (B:s
(3fgGjI GdebGdI GdKGdKI (B: (3GdbhI GdTGeYI ai GdHQhR hGdfahS Edi GdSeGY ajVYa EOQGcgG ddeSehYGJ hGeG GdecQi , aceG EPG hUd ajg Tc s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdChd (B- (3U (B16 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs